THE ANALYSIS OF ORGANIZATION CULTURE USING THE ORGANIZATION CULTURE ASSESSMENT INSTRUMENT (OCAI) BASED ON THE COMPETING VALUES FRAMEWORK (CVF), Case of Pamella Supermarket 3 Yogyakarta - Liyawati, Astri; Lantu, Donald Crestofel (Journal of Business and Management, 2021)
Based on previous researches, corporate culture becomes one of the primary factors in assessing a company's performance in achieving its goals. Author assumes that organization culture is a set of value that can affect habitual behavior as well as the performance of the people within it. To prove this, author conducted a case study on what kind of organization culture is currentially dominant and preferred culture in next years in Pamella Supermarket 3 Yogyakarta using the Six- Dimensional Organization Culture Assessment Instrument (OCAI) Competing Values System. Objective of this study is to provide cultural recommendations according to expectations of all organization actors. The research methodology used is quantitative by distributing questionnaires to all employees (55) people and (45) completed questionnaire. In each dimension, the questionnaire contains eight statements, which are divided into four current cultural statements and four expected cultural statements. Organization culture dominated by the Pamella Supermarket 3 Yogyakarta is Hierarchy (26,5) points, based on the study 's results, Market (23,5) points is the lowest. Pamella Supermarket 3 Yogyakarta dominated by Hierarchy which is characterized by a highly structured place and by the company's formal policies.This organization expects a culture over the next years that is inclined to be dominated by Clan culture with a number of 27,9 points, by growing the Market culture by the sum of 23,7 that is currently embedded in the business. They want a family culture, healthy, responsive, trustworthy, have great mutual confidence. People still want their organization have achievement and result orientation with highly competitive little bit below than the main culture.Pamella Supermarket 3 Yogyakarta will perform training such as understanding, personal development coaching training, team building-learning, bottom-up approach, and apply the new organization climate in order to get expected culture.Keywords: organization culture, OCAI, CVE, hierarchy, market, clan